Electronic Observation: 21st Century Teacher Education - Jackie Glasgow; Susan Jenkins; Kelly Gillespie (The Advocate, 2014)
“A program of brief but frequent classroom walk-throughs has become an increasingly popular strategy in recent years for informally supervising teachers and observing classroom activities” (Protheroe, 2009, p.30). Because walk-through observation has such potential as a catalyst to support both excellent instruction and a positive shift in learning (Walk-Through as Powerful, n.d.), this process is establishing itself as best practice in educational circles (Hopkins, 2010; David, 2008). When real-time observation data are analyzed, used to support reflection and collaborative conversation, and ultimately, when these data become the basis to drive professional learning, the results are clear (Protheroe, 2009). Program initiatives are actualized. Instructional strategies improve. Students become engaged and student achievement increases. This research will discuss the implications of the walk-through observation as a supervisory model in clinical settings for a university teacher education program. Components of effective walk-through observation will be reviewed and results of an electronic application in higher education with be discussed.